A Bursting Liability Evaluation Method Based on Energy Transfer - Yukun Hou; Shankun Zhao; Yang Zhao (Shock and Vibration)
As coal mining gradually moves to deep earth, rock bursts have emerged as one of the main disasters threatening the safety of coal production. It is beneficial to conduct economic and effective prevention and control work by evaluating the bursting liability and improving the bursting liability evaluation system. In this paper, based on the energy transfer model, the relationship between the bursting energy index and the mechanical parameters of coal bodies is obtained by testing the bursting liability of 16 coal seams stratified in three coal mines. According to the bursting energy index and the elastic energy index, the parameter φ is defined to represent the energy release ratio of coal. This paper thus presents a method to evaluate the bursting liability as the product of the energy release ratio and energy transfer ratio and provides a definition for the energy transfer index. The results show that the bursting energy index of coal is closely related to its mechanical parameters. The prepeak deformation energy exhibits a strong positive correlation with uniaxial compressive strength and peak strain. The energy release ratio parameter φ and bursting energy index have high sensitivity and wide applicability. The results of the energy transfer index Ω = βφ are consistent with the results of bursting liability identification, which can better reflect the bursting liability, and can be used as the basis for judgment when the “∗” result is obtained in bursting liability identification. It is anticipated that this approach will become an important evaluation index for bursting liability identification.